Evaluating a digital hybrid training-of-trainers (TOT) approach for lay first responder trauma education in urban Nigeria during the COVID-19 pandemic - Eisner, ZJ; Delaney, PG; Achunine, P; Kulkarni, A; Shaida, F; Smith, N; Onabanjo, S; Popoola, A; Pine, H; Sun, J; Klapow, MC; Raghavendran, K (Elsevier, 2023)
Introduction Road traffic injuries (RTIs) are the largest contributor to the global burden of injury, and in 2016 were among the five leading causes of global disability-adjusted life years (DALYs). In regions with limited emergency medical services (EMS), training lay first responders (LFRs) has been shown to increase availability of prehospital care for RTIs, but sustainable mechanisms to scale these programs remain unstudied. Methods Using a training of trainers (TOT) model, a 5.5-h LFR training program was launched in Lagos, Nigeria. The course was taught in a hybrid fashion with primary didactics using videoconferencing software and practical breakout sessions in-person concurrently. Thirty TOTs proceeded to train 350 transportation providers as LFRs over one month. A 23-question, pre- and post-assessment was administered digitally to assess knowledge acquisition. Participants responded to a five-point Likert survey assessing instruction quality and post-course confidence. Results TOTs scored a median of 56.5 % (IQR:43.5 %,71.7 %) and 91.3 % (IQR:88.0 %,95.7 %) on the pre- and post-assessments, respectively, with bleeding control scores increasing most (+69.4 %). LFR course trainees scored a median of 34.8 % (IQR: 26.0 %, 43.5 %) and 73.9 % (IQR: 65.2 %, 82.6 %) on the pre- and post-assessments respectively, with airway and breathing increasing the most (+48.6 %). All score increases were statistically significant with p < 0.001. All 30 TOT trainers instructed at least one training session after their initial session. LFR participants’ rated confidence in first aid skills went from 3/5 (IQR 3, 4) pre-course to 5/5 (IQR:5,5) post-course, and in emergency transportation it went from 4/5 (IQR:3, 4) to 5/5 (IQR:5, 5), (p < 0.001). LFR course participants rated the quality of education content and TOT instructors to be 5/5 (IQR:5,5). 144 responders provided emergency care in the six-months following training for a total of 351 interventions. Active responders provided a median of 2 (IQR:1,3) interventions. Conclusions This is the first time that a digital hybrid instruction for first responder trainers in low- and middle-income countries has been investigated. Our findings demonstrate negligible attrition, high educational quality ratings, equally effective knowledge acquisition to that of prior in-person courses, and high post-training skill usage. Future work will examine the cost-effectiveness of the training of LFRs and the effect of LFRs on trauma outcomes.